2022
DOI: 10.1080/19336918.2022.2072554
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative and triple-positive breast cancer cells reciprocally control their growth and migration via the S100A4 pathway

Abstract: The study’s aim was to investigate the S100A4-mediated mechanisms of the regulation of tumor cell proliferation and migration in the human triple-positive breast carcinoma cell line MCF-7 (TPBC) and triple-negative breast carcinoma cell line MDA-MB-231 (TNBC). The proliferative activity of TNBC more than doubled during the incubation in the conditioned medium of TPBC. Extracellular S100A4 dose-dependently decreased the proliferative response of TPBC. TPBC negatively impacted the growth of TNBCs during their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Therefore, we performed experiments and found that S100A4 can promote the proliferation of endometrial epithelial cells. In a previous study, S100A4 protein was overexpressed in cultured cancer cells; the results showed that S100A4 protein overexpression did not significantly affect the proliferation of MCF-7 cells but inhibited the proliferation of MDA-MB-231 cells ( 44 ). Similarly, S100A4 was found to regulate cell migration but not cell proliferation in gastric adenocarcinoma ( 20 ).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we performed experiments and found that S100A4 can promote the proliferation of endometrial epithelial cells. In a previous study, S100A4 protein was overexpressed in cultured cancer cells; the results showed that S100A4 protein overexpression did not significantly affect the proliferation of MCF-7 cells but inhibited the proliferation of MDA-MB-231 cells ( 44 ). Similarly, S100A4 was found to regulate cell migration but not cell proliferation in gastric adenocarcinoma ( 20 ).…”
Section: Discussionmentioning
confidence: 96%
“…Breast cancer has much higher morbidity rate than other cancers, so people should take breast cancer seriously ( Ahmad, 2019 ). Triple-negative breast cancer (TNBC) is a subtype of breast cancer ( Dukhanina et al, 2022 ). The disease is characterized by high invasiveness, poor responsiveness to therapy, and difficulty with treatment ( Medina et al, 2020 ; Luna-Dulcey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%